2010
DOI: 10.1097/tp.0b013e3181f9960d
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Donor-Specific CD4+CD25++CD45RA+ Naive Regulatory T Cells in Operationally Tolerant Patients After Pediatric Living-Donor Liver Transplantation

Abstract: This is the first report providing detailed evidence that donor-specific naïve-Tregs were generated and their suppressive properties were upregulated in the peripheral blood of tolerant patients, whereas their frequency was downregulated in intolerant patients. Therefore, we speculate that not only conventional-Tregs play a role in Tx tolerance but also the role of naïve-Tregs is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…Subsequently, data reported by other groups, both in humans and experimental settings, were consistent with this original finding [2][3][4]. We have previously reported that CD4 + CD25 + FOXP3 + Treg-based mechanisms are likely to operate in our pediatric living-donor liver transplant (LDLT) recipients who could stop immunosuppression (IS) (referred to as 'operational tolerance' (OT) [5][6][7][8][9]. In support, a possible role of CD4 + CD25 + FOXP3 + Tregs in OT was reported by others in the settings of liver transplantation (Tx) and renal Tx [10][11][12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Subsequently, data reported by other groups, both in humans and experimental settings, were consistent with this original finding [2][3][4]. We have previously reported that CD4 + CD25 + FOXP3 + Treg-based mechanisms are likely to operate in our pediatric living-donor liver transplant (LDLT) recipients who could stop immunosuppression (IS) (referred to as 'operational tolerance' (OT) [5][6][7][8][9]. In support, a possible role of CD4 + CD25 + FOXP3 + Tregs in OT was reported by others in the settings of liver transplantation (Tx) and renal Tx [10][11][12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 75%
“…If so, it may well be that CD127 dim FOXP3 + cells better reflect the difference of the immune system between the intolerant and weaning groups. Our previous study demonstrated that both conventional Tregs and naïve Tregs were likely to be responsible for OT [8]. Conventional Tregs are most likely a counterpart of murine Tregs documented in the original work of Sakaguchi et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…Современный опыт трансплантации органов подтверждает, что реципиенты действительно неоди-наково реагируют на аллотрансплантат. После срав-нительно короткого периода адаптации с помощью иммуно-супрессивных препаратов [5] одна часть ре-ципиентов способна выйти на толерантность и не от-торгать трансплантат при отмене иммуносупрессии (например, толерантность к трансплантату печени у детей достигает 60% [3,4,6], у взрослых -20% [2,7], тогда как у большей части реципиентов избежать от-торжения удается лишь при постоянном применении медикаментозной иммуносупрессии [5,8].…”
Section: реактивность как фактор индивидуального реагирования иммунноunclassified
“…Therefore, ATG, which we had used for the HLA-identical transplants (described above) and which had been used for DBMT in patients with myeloma and lymphoma [127], of whom several experienced GVHD, was replaced with an anti-CD2 mAb (Medi-507). The latter antibody was known to have potent T-cell-depleting properties as well as costimulatory blockade properties [128,129] [ [143][144][145]; and (5) involvement of T regulatory cells, caused to proliferate by the liver [146].…”
Section: Mixed Chimerism In Hla-mismatched Kidney Transplantationmentioning
confidence: 99%